THE EFFECT OF THE PROBLEM BASED LEARNING ON MATHEMATICAL REASONING AND PROOFING ABILITY IN TERMS OF LEARNING STYLE - Kusumaningtyas, Eryana Ramadani (FKIP Universitas Muhammadiyah Tangerang, 2024)
Mathematics is the main foundation at various levels of education so that students need to be equipped with mathematics in order to have the ability to reason, think logically, systematically and critically in dealing with various problems. There are several factors that cause low reasoning abilities in schools, some of which are the use of learning methods or models while in class. An appropriate learning model for students can improve mathematical reasoning and proving abilities. Learning styles which are divided into three, namely visual, auditory and kinesthetic can also be a factor in low reasoning abilities. The purpose of this study is to identify the impact of the Problem Based Learning model on mathematical reasoning and proof skills, taking into account variations in learning styles. The population in this study were all 8th grade student at SMP Negeri 1 Gatak. The samples taken were two classes taken randomly using simple random sampling technique. This research is a quantitative research with a quasi experiment. The instruments used in this study consisted of a learning style questionnaire, pretest and posttest. The findings from this study are as follows: 1) The use of the Problem Based Learning (PBL) model has a significant impact on students' abilities in mathematical reasoning and proof; 2) Learning style has no effect on students' mathematical reasoning and proving abilities; 3) No interaction was detected between learning models and learning styles in influencing students' mathematical reasoning and proving abilities.